2018
DOI: 10.4236/jcdsa.2018.82007
|View full text |Cite
|
Sign up to set email alerts
|

Skin Manifestations of HIV Infection in Children in Pediatric Services of Conakry University Hospital (Guinea)

Abstract: Introduction: Dermatological manifestations during HIV infection play a diagnostic and prognostic role. They are observed in 83% -98% of patients at the late stage of AIDS and 58% -75% at an early stage of AIDS. The objective of this study was to determine the prevalence of skin diseases in HIV in children, describes the demographic profile and identify key dermatoses. Material and methods: This was a prospective study of descriptive kind conducted from August 25, 2009 to February 25, 2010. It involved childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…Infectious dermatoses were the most observed in 67.5%. These results were consistent with previous works reported from tropical Africa [7][8][9]. Among infectious dermatoses, superficial mycosis represented the majority (47.37%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Infectious dermatoses were the most observed in 67.5%. These results were consistent with previous works reported from tropical Africa [7][8][9]. Among infectious dermatoses, superficial mycosis represented the majority (47.37%).…”
Section: Discussionsupporting
confidence: 93%
“…Our study was particular by the high frequency of cutaneous manifestations in children infected with HIV at 40.5%. The high prevalence of skin diseases during HIV was also reported by several series in sub-Saharan Africa, Ethiopia, and Tanzania (Table 3) [6][7][8][9][10][11]. The average age of the children was sixty months, with their age ranging from 13 months to 120 months in 74.27%.…”
Section: Discussionmentioning
confidence: 55%
“…The prevalence of scabies was within the 3.1-12% range seen in other studies in the cART era. 17,18,20 Nine (31.0%) out of the Inflammatory lesions were more prevalent than infections as corroborated by some studies in the cART era. 18,25 A study reported no change in the prevalence of primary complications of HIV as inflammatory disorders with cART use.…”
Section: Discussionsupporting
confidence: 57%
“…A higher proportion was of school age (6-15 years) (Table 1). Most previous similar studies had younger study populations below 16 years of age, [8][9][10][11][15][16][17][18][19][20] while one study was among adolescents only. 21 The duration of use of cART was adequate to determine its efficacy as the diagnosis of virological failure is viral load ≥1,000 copies/ml after 6 months of effective cART.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, high prevalence of skin and mucocutaneous infections has been reported in Addis Ababa, 72.6% and 79% [6, 7], in Cameroon (68.8%) [10], in Nigeria (72%) [11], and India (67.06%) [9]. Nevertheless, the finding lower than studies from Tanzania (85%) [12], Zimbabwe 88% [13] and, India 93.7% [14] and (88.3%) [15] and higher than a study conducted in Guinea (54.62%) [16]. The variations might be due to the occurrence and pattern of skin infections vary from region to region since specific skin manifestation are common in certain regions of the world [17].…”
Section: Discussionmentioning
confidence: 93%